„BREVILOQUENZA COMPONISTICA“ – ROBERT SCHUMANN AND „FRAUENLIEBE UND LEBEN“ (PART III) - Claudia POP (Studia Universitatis Babeş-Bolyai. Musica)
Robert Schumann, one of the most famous Romantic composers of the first half of the nineteenth century, by his lieder Frauenliebe und Leben made me to feel and to want also, to send this personal reflection of music that addresses the heart of the women to those to whom I’ve extended the positive leaven to approach this music so special: the lied. Driven by the success in singing these lieder by Robert Schumann I decided to behave like a true pedagogue and delimit into the entire study (which contains eight parts), three very important things necessary to approach this genre: